THE FACTORS THAT INFLUENCE THE STUDENTS’ MOTIVATION IN WRITING PERSONAL LETTER - Gusparia Gusparia; Loly Novita; Deny Silvia; Puspa Gundary; Alda Misrimayani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The objective of this research is to find out how is the Students' Motivation in Writing Personal Letter at Grade XI of MA Nurul Falah Airmolek and to find out about what are the Factors that Influence the Students’ Motivation in Writing Personal Letter at Grade XI of MA Nurul Falah Airmolek. The subject of this research consists 20 students at Grade XI MA Nurul Falah Airmolek. The method used in this study is descriptive research. The data of this research were described based on the students’ condition and giving questionnaire then interview. The techniques of data analysis used qualitative analysis. The qualitative analysis is used to count the percentage of the students’ answer the questionnaire. The researcher collects data though observation, questionnaire, interview, and documentation. By analyzing the students’ observation and answer the questionnaire sheet. The researcher obtained the questionnaire result were 73%. It can be concluded that the students’ motivation at grade XI of MA Nurul Falah Airmolek is in good category. The factors that influence the students’ motivation from the internal factors were health got 67%%, interest got 52%, talent got 56%, motivation 58%. The most factors that influence is health. It got 67% of the students were good health. The factors that influence the students’ motivation from the external factors were Family got 62%, school got 87% and surrounding environment got 65%. School is the most factor that influences the students’ motivation in writing personal letter because the teacher's efforts in teaching students such as using interesting methods or media will generate motivation student learning. Key Word: The Students’ Motivation, Writing, Personal Letter